Anxiety / Uncertainty Management in Cultural Communication of Santri Year Teaching of 2021/2022 Al-Muayyad Surakarta Islamic Boarding School - atqiya, ashfiya nur; -, Pawito -; Purwasito, Andrik - (Journal of International Conference Proceedings, 2022)
Anxiety and uncertainty in communication occur when a person enters a new culture in which there is interaction with other people. This study aims to find out how students in the 2021/2021 batch of Al-Muayyad Islamic Boarding School in Surakarta manage anxiety and uncertainty in the context of intercultural communication that occurs in pesantren. The subjects of this study were 12 students who have different cultural backgrounds, genders, and education levels. Using a qualitative descriptive method with a case study approach that uses interviews and researcher observations to collect data. This research looks for three things, namely anxiety and uncertainty before living in boarding school and while in boarding school, management of anxiety and uncertainty before and while living in boarding school, and mindfulness of santri. The student's anxiety and uncertainty before living in boarding school were being away from their parents and worrying about not having friends. The answers that dominate when living in pesantren are that santri experience anxiety and uncertainty about how their parents are at home, cannot have friends when in pesantren, and are bullied by other friends. This study resulted in the findings of good management of anxiety and uncertainty among students so that effective communication occurs.